Improved Irritative Voiding Symptoms 3 Years after Stereotactic Body Radiation Therapy for Prostate Cancer - Rana, Zaker; Cyr, Robyn A.; Chen, Leonard N.; Kim, Brian S.; Moures, Rudy A.; Yung, Thomas M.; Lei, Siyuan; Collins, Brian T.; Suy, Simeng; Dritschilo, Anatoly; Lynch, John H.; Collins, Sean P. (Frontiers in Oncology, 2014)
Background: Irritative voiding symptoms are common in elderly men and following prostate radiotherapy. The impact of hypofractionated treatment on irritative voiding symptoms has not been determined. This study sought to evaluate urgency, frequency and nocturia following SBRT for prostate cancer. Methods: Patients treated with SBRT monotherapy for localized prostate cancer from August 2007 to July 2011 at Georgetown University Hospital were included in this study. Treatment was delivered using the CyberKnife® with doses of 35 Gy-36.25 Gy in 5 fractions. Patient-reported urinary symptoms were assessed using the International Prostate Symptom Score (IPSS) before treatment and at 1, 3, 6, 9, 12 months post-treatment and every 6 months thereafter. Results: 204 patients at a median age of 69 years received SBRT with a median follow-up of 4.8 years. Prior to treatment, 50.0% of patients reported moderate to severe lower urinary track symptoms and 17.7% felt that urinary frequency was a moderate to big problem. The mean prostate volume was 39 cc and 8% had prior procedures for benign prostatic hyperplasia (BPH). A mean baseline IPSS-irritative score of 4.8 significantly increased to 6.5 at 1 month (p < 0.0001), however returned to baseline at 3 months (p = 0.73). The IPSS-irritative score returned to baseline in 91% of patients by 6 months and 96% of patients by 2 years. Transient increases in irritative voiding symptoms were common at one year. The mean baseline IPSS-irritative score decreased to 4.4 at 24 months (p = 0.03) and 3.7 at 36 months (p < 0.0001). In men with moderate to severe LUTS (IPSS > 8) at baseline, the mean IPSS-I decreased from a baseline score of 6.8 to 4.9 at three years post-SBRT. This decrease was both statistically (p < 0.0001) and clinically significant (MID = 1.45). Only 14.6% of patients felt that urinary frequency was a moderate to big problem at three years post-SBRT (p = 0.23). Conclusions: Treatment of prostate cancer